1989
DOI: 10.1002/1097-4679(198909)45:5<809::aid-jclp2270450519>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual rotations on children's Rorschachs

Abstract: Perceptual rotations are responses in which the percept is upside‐down or sideways from the usual position. In a population of 79 children, ages 3 to 15, 75% male, referred to the school psychologist for personality assessment for emotional, behavior, or learning problems; 1 in 9 Rorschach protocols contained at least one rotation. Rotations were not related significantly to reason for referral, learning disabilities, more general learning problems, or organic indicators. Responses showed individual difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Although some research has shown LD children to differ from other populations on the Rorschach (O'Neill, 1989), these differences can be interpreted to reflect degree of disturbance (more severe than normative groups and less disturbed than children who meet the rigorous criteria for special programs for the emotionally disturbed) rather than to a unique distortion of the perceptual world.…”
Section: Methodsmentioning
confidence: 99%
“…Although some research has shown LD children to differ from other populations on the Rorschach (O'Neill, 1989), these differences can be interpreted to reflect degree of disturbance (more severe than normative groups and less disturbed than children who meet the rigorous criteria for special programs for the emotionally disturbed) rather than to a unique distortion of the perceptual world.…”
Section: Methodsmentioning
confidence: 99%
“…A subdermal polyvinyl alcohol implant linearly delivered TFV in plasma at measurable concentrations for more than six weeks [39]. A thin-film polymer devise (TFPD) containing TFV LA demonstrated linear release of 60 days depending on the rate of release [40], and TAF + FTC-loaded nanoparticles showed protection from HIV-1 (Day 4: 80%, Days 7 and 14: 60%, respectively) in humanized BLT (bone marrow-liver-thymus) mice [41]. A release rate of TAF hemifumarate (TAF 2 ) ranging between 0.35 and 0.40 mg/day from multipurpose intravaginal rings (IVRs) has also been reported.…”
Section: La Antivirals Targeting Hiv-1 Rtmentioning
confidence: 99%